Analisis Peran Kurikulum Merdeka dalam Meningkatkan Kemandirian Belajar Siswa di Era Pendidikan Kontemporer - Ma'ruf, Muhammad Hafidh (Universitas Muria Kudus, 2024)
This research aims to analyze the role of the Independent Curriculum in increasing student learning independence in the contemporary education era. The Merdeka Curriculum is the main focus as an effort to adapt learning to the demands of the times which continue to change and develop. In facing complexity and dynamics, the independent learning approach is considered the main foundation for producing graduates who are competent and ready to face future challenges. This research adopts a qualitative approach with descriptive methods to gain a deeper understanding of this phenomenon. By studying literature from various relevant sources, the role of the Independent Curriculum in increasing student learning independence in the contemporary education era is analyzed. The literature review will include an analysis of key concepts related to independent learning, the implementation of the Merdeka Curriculum, and its impact on student learning. It is hoped that the findings of this research can provide a deeper understanding of how the Merdeka Curriculum facilitates and promotes student learning independence. Through comprehensive analysis, this research will identify the key elements of the Merdeka Curriculum that contribute to the development of student learning independence. The implications of this research will provide an in-depth understanding of how the Merdeka Curriculum can be an effective instrument in increasing student learning independence in the contemporary educational era. Furthermore, this research will describe strategies that can be implemented by education stakeholders to maximize the potential of the Merdeka Curriculum in achieving these goals